Analisis Keterlambatan Proyek Menggunakan Metode Fault Tree Analysis pada Proyek Amaris Extension Gorontalo - Raul Fauzan Ishak; Arfan Utiarahman; Apriyanto Pahrun (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Construction project delays are a critical issue frequently encountered during project implementation. These delays may result from various internal factors such as labor shortages, late material deliveries, and incomplete design plans, all of which directly impact the project completion schedule. The Fault Tree Analysis (FTA) method needs to be applied to the Amaris Extension Gorontalo project to identify and mitigate delay-causing factors that pose a risk to timely project completion. The FTA method is used to identify the root causes of project delays by analyzing the basic failure factors. Data were collected through observations, interviews, and project schedules. The analysis was conducted by constructing a fault tree. This study was carried out on the Amaris Extension Gorontalo project with a duration of 365 days. The results of the study indicate that delays were primarily caused by incomplete design planning, labor shortages, and issues related to materials and execution. The Fault Tree Analysis (FTA) method successfully identified the root causes and the top events with the highest probability of occurrence in weeks 19 and 20. These findings provide a solid foundation for improving future project management.